2011
DOI: 10.1194/jlr.d018408
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol profiling of marine microalgae by mass spectrometry

Abstract: ingly important. The methods and pursuit of algae-based fuels also have applications for bioactive lipids and highvalue, lipid-based chemical precursors ( 4,5 ), including polyunsaturated fatty acids (PUFA), carotenes, antioxidants, vitamins, and pigments, which have applications in the pharmaceutical, nutraceutical, and food industries. In all such applications, the methods of analysis, access to desired composition, total yield, and effi ciency with which lipids can be converted to usable products will be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…Generally, the cartridge needs to be conditioned with hexane, and neutral lipids, glycolipids, and phospholipids will be eluted stepwise using chloroform, acetone, and methanol according to the polarity of each fraction. The use of hexane instead of chloroform for the conditioning and elution of neutral lipids has also been reported in order to avoid toxicity of chloroform (Danielewicz et al, 2011). It should be noted that phosphatidylcholines, the cholinecontaining phospholipids, might be retained in the SPE column, which could be verified by comparative profiling of each fraction with raw lipid extracts (Danielewicz et al, 2011).…”
Section: Chemical Characterization Extraction and Fractionation Of LImentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the cartridge needs to be conditioned with hexane, and neutral lipids, glycolipids, and phospholipids will be eluted stepwise using chloroform, acetone, and methanol according to the polarity of each fraction. The use of hexane instead of chloroform for the conditioning and elution of neutral lipids has also been reported in order to avoid toxicity of chloroform (Danielewicz et al, 2011). It should be noted that phosphatidylcholines, the cholinecontaining phospholipids, might be retained in the SPE column, which could be verified by comparative profiling of each fraction with raw lipid extracts (Danielewicz et al, 2011).…”
Section: Chemical Characterization Extraction and Fractionation Of LImentioning
confidence: 99%
“…Hexane extraction results in decreased yields of polar lipids due to its non-polar property. However, the use of hexane would reduce the amount of chlorophyll, which is a major contaminant for lipid extraction (Danielewicz et al, 2011). Different aforementioned solvents have been studied for lipid extraction, and it has been found that chloroform-methanol (1:1) is optimal for a total lipid recovery (Ryckebosch et al, 2012).…”
Section: Chemical Characterization Extraction and Fractionation Of LImentioning
confidence: 99%
See 2 more Smart Citations
“…8,9) In recent years, various strains of Nannochloropsis have been investigated for their biomass production, lipid composition, and content under different growth conditions. 8,[10][11][12][13][14] To further develop them into an integrated photons-to-fuel production platform, high-efficiency transformation methods are necessary.…”
mentioning
confidence: 99%